Determining environmental noise measurement uncertainty in the context of the Italian legislative framework. (November 2016) - Ruggiero, Alessandro; Russo, Domenico; Sommella, Paolo
Highlights: The importance of the uncertainty in environmental noise measurement is discussed. The Italian legislative framework was considered. Decision rules are described to illustrate compliance evaluation near limit values. The uncertainty due to the measurand is calculated for a real dataset. The proposed procedure is easily integrated into noise level meter firmware. Abstract: This paper aims to demonstrate the importance of uncertainties in the measurement of environmental noise in the context of Italian legislation on noise pollution focusing the attention on the variability of the measurand as a source of uncertainty and offering a proposal for the evaluation of uncertainty for traffic noise measurement. In particular, drawing on a real traffic noise dataset, firstly outliers are eliminated from the actual noise measurements using an outlier detection algorithm based on K -neighbors distance and then uncertainty range is estimated with the bootstrap- t method. Since the original sequence was Gaussian, this range was compared with the confidence interval of the mean ± standard deviation interval and two intervals were almost coincident.